The resveratrol oligomers, cis- and trans-gnetin H, from Paeonia suffruticosa seeds inhibit the growth of several human cancer cell lines. (1st July 2015) - Gao, Ying; He, Chunnian; Ran, Ran; Zhang, Dabing; Li, Dawei; Xiao, Pei-Gen; Altman, Elliot
Abstract: Ethnopharmacological relevance: Paeonia suffruticosa Andrews (PSE) is a well-known Chinese medicine that has been widely used as an anti-tumor, anti-oxidative and anti-inflammatory agent. cis - and trans -gnetin H are two resveratrol oligomers isolated from the seeds of PSE. Although resveratrol is widely considered to be one of the most valuable natural chemopreventive agents and there are numerous studies on the antitumor activities of resveratrol, little is known about the antitumor properties of cis - and trans -gnetin H. Materials and methods: The inhibitory effects of cis - and trans -gnetin H in different human cancer cell lines were assessed using fluorescent viability tests. Cytotoxicity in human lung and breast cancer cells was detected via nuclear condensation, cell permeability, and changes in the mitochondrial membrane potential (∆ψm). Apoptosis in human lung and breast cancer cells was assessed by flow cytometry, a luminescence assay and high-content screening analysis. Finally, a xenograft mice model was used to examine the efficacy of cis -gnetin H on lung tumors. Results: cis - and trans -gnetin H have superior activity in inhibiting the proliferation of four human cancer cell lines, A549 (lung), BT20 (breast), MCF-7 (breast) and U2OS (osteosarcoma), and promote cell apoptosis, while having a minimal effect on two normal human epithelial cell lines, HPL1A (lung) and HMEC (breast) used as controls. cis - and trans -gnetin H promote apoptosis by releasing mitochondria cytochrome c, activating caspase 3/7 and inhibiting NF-κB activation. Flow cytometry analysis shows that cis - or trans -gnetin H arrested the cell cycle of cancer cells at the G0–G1 phase. Moreover, cis -gnetin H suppressed the growth of xenograft lung tumors in mice. Conclusion: Collectively, our findings demonstrate the promise of the natural compounds cis - and trans -gnetin H as candidates for cancer chemotherapy agents. Graphical abstract: